A unified materials approach to mitigating optical nonlinearities in optical fiber. II. B. The optical fiber, material additivity and the nonlinear coefficients. (11th December 2017) - Dragic, Peter D.; Cavillon, Maxime; Ballato, Arthur; Ballato, John
Abstract: The purpose of this paper, Part IIB in the trilogy [ Int J Appl Glass Sci . 2018 (not available); Int J Appl Glass Sci . 2018 (not available); Int J Appl Glass Sci . 2018 (not available)], is to describe the continuum models employed to deduce the effects of differential thermal expansion in the clad optical fiber in addition to the nonlinear optical behaviors at high intensities of light. In this continuation of Part IIA, more of the state‐of‐the‐art in W‐S‐based continuum material models are reviewed here with specific examples provided based on canonical material systems suggested from the findings of Part I and treated in detail in Part III. Part IIB pays particular attention to the optical fiber and its nonlinearities.